Association rules mining applied in the animal movement exploratory analysis - Fontes, S. G.; Côrrea, P. L. P.; Stanzani, S. L.; Morato, R. G. (Anais do Symposium on Knowledge Discovery, Mining and Learning (KDMiLe), 2019)
The animal movement analysis determines the animal behavior, which is the basis for understanding the interaction between species and the environment and to guide actions of preservation and conservation. The challenge is how to explore this movement data, getting indications about how the animal behaves over time and space. In this sense, a framework to animal movement exploratory analysis is presented, that combines algorithms for spatiotemporal data analysis and association rules mining, as a first step to answer questions related to animal behavior. We performed the framework’s evaluation in the exploratory analysis of monitored monkeys (Cebus capucinus) in the Panamá.